(untitled) (UKLO Proceedings, 2026)
Introduction: Artificial intelligence (AI) has completely transformed our world, fundamentally changing many areas of our daily lives. While natural language processing (NLP) technologies have become part of our day-to-day live, one of the sectors most significantly affected appears to be education. However, one area that remains underexplored is AI in pedagogical stylistics – i.e., the practical use of AI models in teaching literature within the English language classroom. Methods: Recognizing a research gap, this qualitative paper explores how teachers can incorporate AI into pre-, during-, and post-reading activities. Drawing on existing literature and personal experience with AI use, the study proposes practical applications and activity designs, with a focus on instructional integration of AI. Results: The paper proposes a series of practical AI-based activities designed to strengthen students’ EFL (English as a Foreign Language) skills while leveraging the immense potential of these technologies in language and literature education. Discussion: By addressing the gap in AI’s role in pedagogical stylistics, the paper emphasizes AI’s potential to improve engagement, comprehension, and critical thinking in literature-based EFL instruction.